Mixed mode interlaminar fracture of carbon nanotubes enhanced epoxy/glass fiber composites - Silva, H. (2015)
Present paper studied the improvement of the fracture toughness under mixed mode loading obtained by using carbon nanotubes reinforcement in fiber glass mats/epoxy laminates. Mixed-mode bending tests were performed considering different loading ratios GII/GI. Laminates were manufactured using the epoxy resin Biresin® CR120 reinforced with fiber glass triaxial mats ETXT 450 and multiwalled carbon nanotubes with 98% of carbon. It was observed that the total fracture toughness increases linearly with the mode II loading component and that linear mixed-mode fracture criteria reproduces the GI versus GII relationship. The incorporation of small quantity, up to 0.5%, of carbon nanotubes into matrix improves significantly mixed-mode fracture toughness.